Anatomy & Massage - Mármol, J.; Jacomet, A. (Meyer & Meyer Sport (UK) Ltd., 2018)
A massage helps in all situations. Massage techniques can be used not only for relaxation, but also in sports—where the right massage technique can be used for regeneration, rehabilitation, and injury prevention. The unique mixture of photos and anatomical drawings makes it incredibly easy to understand every technique and put them into practice.